Humanizing grief in higher education narratives for allyship and hope - Sieben, Nicole; Shelton, Stephanie Anne, 1978- (New York, NY : Routledge, 2021)
By showcasing asset-based approaches inspired by individual reflection, research, and experience, this volume offers a fresh and timely perspective on grief and trauma within higher education and illustrates how these approaches can serve as opportunities for hope and allyship. Featuring a broad range of contributions from scholars and professionals involved in educational research and academia, Humanizing Grief in Higher Education explores the varied ways in which students, scholars, and educators experience and navigate grief and trauma. Set into four distinct parts, chapters deploy personal narratives situated within interdisciplinary and transdisciplinary research frameworks to illustrate how issues such as race, gender, socio-economic class, and politics intersect with experiences of personal and professional grief in the academy. A variety of intersectional fields of study - from positive psychology, counselling, feminist and queer theories, to trauma theory and disability studies - inform an interdisciplinary framework for processing traumatic experiences and finding ways to hope. These narrative explorations are positioned as key to developing a sense of hope amongst the grieving and those supporting them. This text will benefit researchers, doctoral students, and academics in the fields of Higher Education, teacher education, trauma studies, and mental health education. Those interested in positive and educational psychology, as well as grief counselling in adults, will also enjoy this volume. Finally, this collection serves as a companion for those who find themselves grappling with losses, broadly defined.
OCLC-licensed vendor bibliographic record.
Keywords: College students -- Psychology; College teachers -- Psychology; Education, Higher -- Psychological aspects; College teaching -- Psychological aspects; Grief; Narrative inquiry (Research method); EDUCATION / Higher